2013
DOI: 10.7314/apjcp.2013.14.2.1067
|View full text |Cite
|
Sign up to set email alerts
|

Hiwi Knockdown Inhibits the Growth of Lung Cancer in Nude Mice

Abstract: Hiwi, a human homologue of the Piwi family, plays an important role in stem cell self-renewal and is overexpressed in various human tumors. This study aimed to determine whether an RNA interference-based strategy to suppress Hiwi expression could inhibit tumor growth in a xenograft mouse model. A rare population of SSC lo Alde br cells was isolated and identified as lung cancer stem cells in our previous study. Plasmids containing U6 promoter-driven shRNAs against Hiwi or control plasmids were successfully est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Further immunohitochemistry analyses confirmed that the hiwi blockage also induced a significant suppression in ALDH-1 positive cells in xenograft tumor samples (Liang et al, 2013). Since ALDH-1 is a confirmative marker of the lung cancer stem cells (Liang et al, 2012), it implied that delivery of shRNA-mediated Hiwi gene silencing resulted in the decreased number of lung cancer stem cells and suppressed tumor growth in nude mice.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Further immunohitochemistry analyses confirmed that the hiwi blockage also induced a significant suppression in ALDH-1 positive cells in xenograft tumor samples (Liang et al, 2013). Since ALDH-1 is a confirmative marker of the lung cancer stem cells (Liang et al, 2012), it implied that delivery of shRNA-mediated Hiwi gene silencing resulted in the decreased number of lung cancer stem cells and suppressed tumor growth in nude mice.…”
Section: Discussionmentioning
confidence: 79%
“…and the suppression of hiwi inhibited the growth of gastric cancer cells and induced cell cycle arrest in G2/M phase (Liu et al, 2006). Whereas, hiwi knockdown inhibits the growth of lung cancer in nude mice (Liang et al, 2013). These results suggest that hiwi may be involved in the tumorigenesis of various cancers and is a potential target for cancer therapy.…”
Section: Introductionmentioning
confidence: 87%
“…Yang et al demonstrated that the inhibition of HIWI expression was able to significantly reduce tumor growth in a xenograft mouse model (35). Furthermore, immunohistochemical analyses suggested that downregulation of HIWI was associated with a reduced number of aldehyde dehydrogenase (ALDH)-1 positive cells in xenograft tumor samples (36).…”
Section: A B C D Discussionmentioning
confidence: 99%
“…In addition, recent data also suggest a role for Aub in tumorigenesis, [34][35][36][37] stem cell identity renewal 17 and in the nervous system. 38 Characterizing the role and the genetic interactions of aub in the different tissues is essential.…”
Section: Discussionmentioning
confidence: 99%